Experimental tests and theoretical analysis for mechanical behaviors of side wall opening construction in mined excavation subway station - Hu, Zhinan; Mao, Hongtao; Zhang, Lixin; Liu, Zhichun (Frontiers in Earth Science, 2023)
The connection of subway stations to surrounding underground spaces inevitably involves opening construction in the existing underground structure. Especially when there is no reserved condition, the opening construction can strongly impact the existing underground structure. In this study, three-dimensional numerical simulation, model test, and theoretical analysis are used to analyze the mechanical behaviors of side wall opening construction in a mined excavation subway station—Xuanwumen Station of Beijing Subway Line 4. Based on the deformation and stress characteristics of the existing side wall structure, two different reinforcement measures are compared. It is found that the vertical and horizontal deformations of the existing structure caused by opening construction is –1.58 and –1.79 mm, respectively, which are lower than the subway deformation control requirements (3 mm). However, the first and third principal stress increments are 2.14 and –4.62 MPa, respectively, which are markedly higher than the control requirement (10%). A “two-step opening” method is proposed for side wall opening construction in underground structures based on the solution of complex function to the orifice problem. This theoretical method is validated by numerical simulations and model tests, achieving highly consistent results. The allowable ultimate span of side wall opening is 5.75 m without reinforcement. Findings of the present study provide a reference for the design and construction of side wall openings in similar underground spaces.